Seeing (as) the Eroticized and Exoticized Other in Spanish Im/migration Cinema: A Critical Look at the (De)Criminalization of Migrants and Impunity of Hegemonic Perpetrators - Maureen Tobin Stanley (Studies in 20th & 21st Century Literature, 2019)
This article examines cinematic perspective in six Spanish im/migration films to show that by resituating the identification from an alignment with that of a hegemonic character (who accepts the systematic bias that confers impunity to perpetrators) to identification with a criminalized migrant subject, these films 1) denounce systemic intersectionality that confers impunity to perpetrators and criminalizes the racialized and/or feminized other and 2) aim at fostering empathy in the hegemonically identified viewer. Parameters for the selection of the six films are: immigration to Spain, African (whether geographic or ethnic) origins, eroticization of the migrant, objectification/(ab)use/commodification/victimization of the Other, criminalization of the Other while conferring impunity to a malfeasant representative of the hegemony and, ultimately, an identification (be it fleeting) between a character of the Spanish in-group and the migrant subject. The cinematic narratives include three canonical films from the 1990s Cartas de Alou (Letters from Alou, Montxo Armendáriz, 1990), Bwana (Imanol Uribe, 1996), Flores de otro mundo (Flowers from Another World, Icíar Bollaín, 1999), Princesas; and three from the 2000s (Princesses, Fernando León de Aranoa, 2005), 14 kilómetros (14 Kilometers, Gerardo Olivares, 2007) and Retorno a Hansala (Return to Hansala, Chus Gutiérrez, 2008). In essence, this article investigates the ways in which cineastes problematize the hegemonic gaze regarding the migrant Other and depict the transformation from looking at migrants as a criminal “them” to seeing them as a human “us.”
Keywords: Spain; race; racism; gender; immigration; cinema; gaze; empathy; erotic; exotic; extralegal; illegal; impunity; immunity; stereotypes; the Other